Minimal change disease associated with thyroid cancer: a case report - Cai, Xiaoyi; Wu, Yuenv; Wan, Qijun; Zhang, Xiuli (Frontiers in Medicine, 2023)
A patient complaining of edema of the face and lower extremities was admitted to the nephrology department for nephrotic syndrome. Renal biopsy revealed findings of minimal change disease (MCD). Thyroid ultrasound showed a hypoechoic 16 × 13 mm nodule in the right lobe, suspicious of malignancy. Later, total thyroidectomy confirmed the diagnosis of papillary thyroid carcinoma (PTC). After surgery, MCD remitted rapidly and completely, strongly suggesting the diagnosis of MCD secondary to PTC. We report here the first adult case of the paraneoplastic finding of MCD secondary to PTC. Additionally, we discuss the possible role of the BRAF gene in the pathophysiology of PTC-associated MCD in this case and highlight the importance of tumor screening.